Modern Rolling Stock as a Pillar of the Technological Triangle (Current Problems in Rail Vehicles, 2025)
This conference is an established forum for presenting novel insights and current technological advances in rolling stock. Both practical and scientific evidence underscores the significance of this sector, with its innovations contributing to the growing popularity of rail transport. This article, however, offers a cautionary perspective. It serves as a warning for those responsible for ordering these vehicles under public service obligations, as well as those who build and manage the supporting infrastructure. While many innovations are undoubtedly beneficial, some can complicate technological integration and pose significant challenges for transport technologists. The pivotal element in this regard is the uniformity among the transport infrastructure, the vehicles used, and the customer's operational concept along a specified route. Collectively, these are referred to as the technological triangle. This article presents practical examples of effective solutions and their real-world impact, focusing on the synergistic effect of modernizing rolling stock and railway infrastructure and linking these aspects with the timetable and operational concept.
Keywords: public service obligation; rolling stock; technological period; operational concept; railway infrastructure